Comparison of suicidal ideation, suicide attempt and suicide in children and young people in care and non-care populations: Systematic review and meta-analysis of prevalence. (November 2017) - Evans, Rhiannon; White, James; Turley, Ruth; Slater, Thomas; Morgan, Helen; Strange, Heather; Scourfield, Jonathan
Abstract: Suicide in children and young people is a major public health concern. However, it is unknown whether individuals who have been in the care of the child welfare system are at an elevated risk. Care is presently defined as statutory provision of in-home care (e.g. child living with birth family but in receipt of legal order involving supervision by social workers) or out-of-home care (e.g. foster care, residential care and kinship care). This paper presents a systematic review and meta-analysis comparing the prevalence of suicidal ideation, suicide attempt and suicide in children and young people placed in care with non-care populations. A systematic search was conducted of 14 electronic bibliographic databases and 32 websites. Of 2811 unique articles identified, five studies published between 2001 and 2011 met the inclusion criteria. Studies reported on 2448 incidents of suicidal ideation, 3456 attempted suicides and 250 suicides. The estimated prevalence of suicidal ideation was 24.7% in children and young people in care compared to 11.4% in non-care populations. The prevalence of suicide attempt was 3.6% compared to 0.8%. Two studies reported on suicide. Suicide risk in children and young people in care was lower in one study (0% vs 0.9%) and higher in the second (0.27% vs 0.06%). The results of the systematic review and meta-analysis confirm that suicide attempts are more than three times as likely in children and young people placed in care compared to non-care populations. Targeted interventions to prevent or reduce suicide attempt in this population may be required. Further comparative studies are needed to establish if children and young people in care are at an elevated risk of suicidal ideation and suicide. Highlights: Global problem of suicidal ideation, suicide attempt and suicide among young people Unknown if young people in care are at an elevated risk. Systematic review comparing prevalence between care and non-care populations Suicide attempt is more than three times as likely among those in care. Further comparative studies are required.